EVALUASI PROGRAM KELUARGA HARAPAN DI DESA CIPETE, KECAMATAN CILONGOK, KABUPATEN BANYUMAS - Chamid Sutikno; Ariesta Amanda; Misbahudin Misbahudin (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
The Family Hope Program is a community protection program organized by the Government of Indonesia since 2007. Through a system of providing sustainable assistance, this program aims to help communities meet their basic needs and stop the poverty line. Of course in its implementation can not be separated from the success and shortcomings, so evaluation must be carried out. With qualitative descriptive methods, interview data collection techniques, observation and documentation, as well as data validity triangulation techniques, this study aims to evaluate the Family Hope Program in Cipete Village, Cilongok District, Banyumas Regency. The results of the study indicate that the Family Hope Program can run well, as can be seen from the initial meeting, disbursement of aid, updating of Beneficiary data and verification of program participants' commitments. In addition, recommendations were obtained that this program is feasible to continue with improvements in the data updating process, considering that there are still underprivileged communities who have not been touched by the program, and beneficiaries who are no longer eligible to receive assistance. In this case, a better coordination and supervision system is needed so that the objectives of this program can be achieved effectively and efficiently.